Eksperimen Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) dan Think Pair Share(TPS) Terhadap Hasil Belajar Matematika Ditinjau dari Kemampuan Awal(Penelitian Eksperimen Kelas XI Semester Gasal Di SMK MUHAMMADIYAH 01 Sambi Boyolali Tahun Ajaran 2016/2017) - Fadilah, Firda Nur; , Muhammad Noor Kholid, S.Pd, M.Pd (2016)
This study aimed to analyze: (1) differences in the effect of the application of learning model Numbered Head Together (NHT), Think Pair Share (TPS) and Expository the learning outcomes of mathematics, (2) differences in the influence of the initial ability of students to the learning outcomes of mathematics, (3 ) the interaction between the application of the learning model Numbered Head Together (NHT), Think Pair Share (TPS) and Expository with the level of prior knowledge on learning outcomes in mathematics. This research was quantitative with quasi-experimental research design. The population in this study were all students of class XI SMK Muhammadiyah 01 Sambi, Boyolali Academic Year 2016/2017. The sampling technique in this study using cluster random sampling. Methods of data collection using achievement test and documentation. Data were analyzed using two-way analysis of variance with different cells. The results of the analysis with a significance level of 0.05 indicates that: (1) there are differences in the effect of learning model Numbered Head Together (NHT), Think Pair Share (TPS) and Expository the mathematics learning outcomes with Fa=3.4437 (2) there are differences in influence ability levels beginning with the results of learning mathematics by Fb = 16.4781 (3) there is no interaction between the learning model Numbered Head Together, Think Pair Share (TPS) and Expository with the level of prior knowledge on learning outcomes of mathematics, with Fab=0.7343. Keywords: expository, math learning outcomes, initial capabilities, numbered heads together, think pair share